Secure and remote firmware update of cellular IoT micro devices with limited resources. (21st October 2019) - Cezayirli, Ahmet
Typically, cellular internet of things (IoT) devices are spread over very large areas, usually countrywide or even worldwide. This makes the firmware update operation a troublesome and costly task, and it is usually avoided as long as possible. However, due to some bugs detected in the core software and/or some significant performance enhancements developed after the release of the device, the need for a firmware update becomes inevitable. We propose a new methodology in order to fulfil the firmware update remotely in an easy and secure way for especially the devices with quite limited resources, such as very small RAM and low processing power. We utilise multimedia messaging service (MMS) functions, and send the firmware to the remote cellular IoT devices as encrypted attachment. The preparation steps of the attachment are explained in detail, a handshaking mechanism is established and all are tested on a particular hardware. Some important remarks are also provided, so that major practical aspects of the methodology would be readily available in implementing it on hardware/software architectures of new IoT devices.